A review for the automatic methods of plant's leaf image segmentation. (29th January 2020) - Sharma, Shivalika; Gupta, Abhishek
Various plant species had disappeared and many are on the verge of disappearing. Our economy highly depends on agricultural productivity. Plants play an important role in the agriculture field. Plant's leaf segmentation has become an important task in the agricultural fields. In the leaf segmentation process, a few generalised steps are followed such as leaf image acquisition, leaf image pre-processing, feature extraction and leaf image segmentation. It is important to identify and differentiate various features from a noisy background. Feature extraction is the intermediary step to identify the features in leaves such as leaf area, leaf colour, leaf texture, etc. There are various techniques used for both feature extraction as well as segmentation of leaves like edge detection technique, K-means clustering techniques, artificial neural network-based techniques, etc. This paper presents a review of some methods used for the segmentation of leaf based on the available literature.